Pesticides and risk assessment in Shanghai fruit and raw eaten vegetables. Issue 4 (2nd October 2021) - Si, Wen-Shuai; Wang, Shou-Ying; Zhang, Yao-Dan; Kong, Cong; Bai, Bing
ABSTRACT: A database of 392 pesticides established by an Ultrahigh performance liquid chromatography-tandem Q/Orbitrap high-resolution mass spectrometer (UPLC-Q/Orbitrap-HRMS) was used to screen multiple residues of pesticides in fruit and raw eaten vegetables from planting farms in Shanghai. Risk assessment was conducted with the screened results of the determined pesticides as to evaluate food safety. In 95% of the samples, one or more pesticides had a content below the maximum residue limits (MRLs) as set in the national Chinese standard. The co-occurrence of multi-residues of pesticides was more severe in peach and muskmelon, when compared with other food. All hazard index values of different groups were in the range of 0.19% to 12.3%, demonstrating that chronic dietary risk of studied fruits and raw eaten vegetables is low and the studied food samples were safe for human consumption in terms of these detected pesticides.